Application of Acoustic Scanning Technology in Quality Analysis of IGBT Module - LI Han; ZENG Xiong; XU Ninghua; HE Xinqiang; FENG Huiyu; LI Liangxing (Kongzhi Yu Xinxi Jishu)
It introduced the principle of acoustic scanning microscope (SAM), described the undamaged detection functions of SAM in IGBT modules with different modes. With this technology, it not only can discover interface defects (like hole and detachment) easily, but also can find structure defects by analysis of surface evenness, modulation of internal composition and thickness measurement, and the characterization of defects are very important to quality assessment in IGBT modules.